2021
DOI: 10.1111/gcb.15615
|View full text |Cite
|
Sign up to set email alerts
|

Linkage between microbial shift and ecosystem functionality

Abstract: Exploring the linkage between microbial shifts and ecological processes or ecosystem functionality is a central focus in microbial ecology, but faces considerable obstacles, including the gap between DNA‐based information and biochemical processes, as well as the asynchronization in microbial taxonomic shifts and their functionality change. Despite these issues, the well‐established linkage between functional genes (reflecting genetic potential) and carbon release via laboratory incubation (reflecting field po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…An incubation study with 405 permafrost soil from the Tibetan Plateau found that CO2 release after thawing showed a positive relationship with functional gene abundance for C degradation (Chen et al, 2020) without changing the composition of the microbial community. In general, high-altitude ecosystems differ from high-latitude ecosystems by having lower contents of OM and ice, with consequences for microbial community composition (Wang and Xue, 2021). In the present study, there were clear differences in the kinetics of gaseous product accumulation, both for CO2 and CH4.…”
Section: Total C Mobilisationmentioning
confidence: 45%
“…An incubation study with 405 permafrost soil from the Tibetan Plateau found that CO2 release after thawing showed a positive relationship with functional gene abundance for C degradation (Chen et al, 2020) without changing the composition of the microbial community. In general, high-altitude ecosystems differ from high-latitude ecosystems by having lower contents of OM and ice, with consequences for microbial community composition (Wang and Xue, 2021). In the present study, there were clear differences in the kinetics of gaseous product accumulation, both for CO2 and CH4.…”
Section: Total C Mobilisationmentioning
confidence: 45%